The first species of Cotithene Voss (Coleoptera: Curculionidae: Curculioninae) from Amazonian Brazil, with notes on its role as a pollinator of Evodianthus funifer (Poit.) Lindm. (Cyclanthaceae) - Valente, Roberta M.; Da Silva, Paulo A. L.; de Medeiros, Bruno A. S. (Zootaxa, 2019)
Cotithene gorayebi Valente, da Silva & de Medeiros, sp. nov. is the first species of Cotithene Voss, 1940 described from the Amazonian forest in Brazil. The new species differs from other described species of Cotithene by its integument color pattern dissimilar between sexes and by the procoxal cavities separated by only a narrow septum in both male and female. It furthers differs by the unique morphology of male and female genitalia. A previously published key and phylogenetic matrix to Cotithene species were each modified to include the new species. The historical trajectory of host associations (inflorescences of Cyclanthaceae) in Cotithene is reanalyzed with the inclusion of the host of the new species. Previously known species are believed to be non-pollinators of various Cyclanthaceae; however, field observations of adults of the new species on inflorescences in anthesis of Evodianthus funifer (Cyclanthaceae) strongly suggest that this may be the first species of Cotithene known to play a role as a pollinator of Cyclanthaceae.